Endomyocardial fibrosis: is it a systemic disease? - Juergen Freers; Victoria Masembe; Rolf Schmauz; Frederick Kidaaga; Harriet Mayanja-Kizza (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Background: Patients with endomyocardial fibrosis (EMF) characteristically present with gross ascites and absent or minimal pedal oedema. This has long puzzled clinicians, especially since this clinical picture remains the same regardless of whether there is left, right or biventricular ventricular heart failure. The development of ascites, therefore, may not be directly and solely related to changes in the heart, but to local changes in the peritoneum. In order to investigate this possibility we performed peritoneal biopsies on 28 EMF patients. Methods: Successful peritoneal biopsies were performed on 28 EMF patients and 11 age-matched healthy controls who had died in road accidents. Results: All 28 patients (100%) showed complete or partial peritoneal fibrosis. Twenty Six (93%) had additional signs of chronic peritonitis characterised mainly by lymphocytes (92%) eosinophils (27%) and plasma cells (23%). Neutrophils were not seen. Vascularisation was common (87%) with an increase in capillaries and granulation tissue. Other components were Russel bodies (50%), deposits of fibrin (50%) and haemosiderin pigment (32%). Only two samples showed fibrosis without signs of inflammation. None of the controls showed any of these changes. Conclusion: Peritoneal fibrosis was found in all and peritonitis in most of our EMF patients. This suggests that pathology of EMF is not confined to the heart but also involves the peritoneum. This local peritoneal inflammation may explain why marked ascites is often present with little or no peripheral oedema, and why conventional heart failure treatment is of limited value.